Hubungan menonton video mukbang autonomous sensory meridian response, keinginan makan dan uang saku dengan asupan makan dan status gizi mahasiswa - Margawati, Ani; Wijayanti, Hartanti Sandi; Faizah, Nur Azkiyati; Syaher, Miladita Ilmanda (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: College students are susceptible to the effects of obesity due to the wrong lifestyle. Nowadays, watching Mukbang autonomous sensory meridian response (ASMR) video has been trending habit especially among college students. The food video increases visual stimulus will stimulate the brain. The audio stimulus can influence eating behavior when hungry. Objectives: The aims of the study were to determine the correlation of watching Mukbang ASMR video and pocket money with food intake and nutritional status of Diponegoro University students.Methods: This study was an observational research with cross-sectional design. Subjects were 60 Diponegoro University student aged 20 – 23 years old, selected by consecutive sampling. Independent variables is the habit of watching Mukbang ASMR video, food craving, and pocket money and the dependent variable are food intake and nutritional status by BMI. Data collected were done by interviews direct questionnaire about the habit of watching Mukbang ASMR video, FFQ, FFQ fast food and 3 x 24 hour recall and measure weight and height. Analysis using Rank Spearman and Chi Square correlation test.Results: This study found the reason subject watched Mukbang ASMR was because the sound produced by the video was satisfying. Watching Mukbang ASMR videos when hungry is significantly related to the subject's desire to eat (p = 0.044). The frequency of watching, the desire to eat after watching the ASMR Mukbang video and pocket money are not related to the adequacy of nutrient intake and nutritional status of the subject.Conclusion: Watching ASMR Mukbang videos and pocket money has no effect on student intake and nutritional status.